Perspectives of US Youth During Initial Month of the COVID-19 Pandemic - Waselewski, Eric (Ann Fam Med, 2021)
PURPOSE: Asymptomatic youth in the United States acting as “silent spreaders” during the coronavirus disease 2019 (COVID-19) pandemic are an ongoing public health concern, particularly given their depiction as unengaged with recommendations. Our goal was to understand the knowledge, beliefs, and experiences of US youth at the onset of the COVID-19 pandemic. METHODS: We posed 2 open-ended surveys to the national MyVoice text message cohort of youth, aged 14-24 years. On March 6, 2020, 4 questions were asked regarding knowledge and experiences during the COVID-19 pandemic with 3 questions repeated on March 20, 2020. Qualitative responses were coded using thematic analysis and summarized with descriptive statistics. RESULTS: Of 1,174 youth, 1,087 responded to at least 1 question (response rate of 88%). The average age of respondents was 19 (SD 2.8) years with 52% female and 56% non-Hispanic White respondents. On March 6, 2020, most (70%) respondents reported knowing about COVID-19 and primarily cited the news (46%) as their source of information. Nearly all (95%) respondents reported impact by March 20, 2020, and respondents expressing worry increased from 25% to 51%. In both surveys, worried youth primarily cited concern for others (26% and 34%). Regarding preparation, respondents primarily reported doing nothing (36%) on March 6, 2020, and practicing social distancing (50%) on March 20, 2020. CONCLUSIONS: Many youths in our sample are engaged with the COVID-19 pandemic and most are feeling knowledgeable, are concerned about its impacts on others, and are practicing social distancing. Sustained public health efforts should focus on maintaining youth engagement with accurate public information and youth-centered messaging promoting prevention measures to protect the health and well-being of youth and their friends and family.